+TUO project: low cost 3D printers as helpful tool for small communities with rheumatic diseases. Issue 5 (17th August 2015) - Ostuzzi, Francesca; Rognoli, Valentina; Saldien, Jelle; Levi, Marinella
Abstract : Purpose: – This paper aims to present a pilot study's aims to identify opportunities and limits deriving from the use of low-cost 3D printing (3DP), fused deposition modelling (FDM), open-source technologies in co-design and co-production processes involving persons with rheumatic diseases (RDs). Design/methodology/approach: – In the paper, the authors outline why the use of low-cost, entry-level FDM can be meaningful for this scenario, implying a complete sharing of the design and the production phases of small assistive devices. The +TUO process is composed of several stages, among which the generative session represents the core. Findings: – This study highlights as the introduction of this low-cost technology in co-generative processes with people with RDs is a real challenge that can lead to new products and solutions, and that can sustain a social and local manufacturing approach for people facing a specific disablement. Research limitations/implications: – This research is a first step of a broader research, new researches are going to explore further details related with the technology and of the adopted method. Practical implications: – Involving actively, the end user during the creation process can bring advantages such as meeting more precisely their needs and create innovative products, as shown in the text. Social implications: – For people living with RDs, an occupation is important to sustain a process of empowerment. Adopting assistive devices supports daily activities and facilitates the occupation. Originality/value: – +TUO is a pilot study that explore a topic already discussed in the scientific arena, without focusing on the specific use of low-cost 3DP technologies.